Population data and phylogenetic analysis of 37 Y-STR loci in the Hui population from Yunnan Province, Southwest China - Xiufeng Zhang; Kunya Li; Yifan Duan (Taylor & Francis Group, 2023)
Background Previous studies of the genetic polymorphism of the Y-chromosomal short tandem repeat (Y-STR) of Huis were focussed on the northwest of China. However, the population genetic characteristics of Chinese Hui residing in Yunnan province, Southwest China, remain unclear. Aim To provide genetic data for 37 Y-STRs in the Chinese Hui population of Yunnan province, as well as to investigate population genetic relationships between the Chinese Hui and another 26 populations from China and neighbouring countries. Subjects and methods In total, 326 unrelated healthy male individuals were genotyped using the GoldeneyeTM Y Plus PCR Amplification Kit. Genetic relationships between different populations were analysed using YHRD's AMOVA tools. Results A total of 279 haplotypes were detected, out of which 244 were unique. The overall haplotype diversity (HD) and discrimination capacity (DC) were 0.9989 and 0.8611, respectively. The gene diversity (GD) ranged from 0.0544 (DYS645) to 0.9656 (DYS385). Conclusions The population comparison indicated that Muslim populations (Hui, Salar and Uighur) showed significantly more genetic affinity than other populations. Our results could be applied in forensic practice and population genetic studies.